1993
DOI: 10.1108/eum0000000000844
|View full text |Cite
|
Sign up to set email alerts
|

Libraries Versus Users? How and How Not to Deter Library Users

Abstract: Information technology allows libraries to provide access vo resources and information services far beyond the limits of their own collections. The users′ needs for information and recreation are the primary concern of libraries, yet librarians realize that a significant proportion of the population rarely or never use libraries, while library users experience frustration or failure when using their library. Examines various factors which influence the attitude of individuals or groups to libraries and conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…From this point of view, it is possible to explain the positive relationship between the large-sized libraries' implementation of a takeaway loan scheme and organizational attractiveness. In this case, digital tools and ICTs are exploited to overcome the limitations imposed by Covid-19 (Ashiq et al, 2022), giving a sense of normality to the exchange between users and libraries and adding to the users' experience through positive emotions and sensations (Coker, 1993).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From this point of view, it is possible to explain the positive relationship between the large-sized libraries' implementation of a takeaway loan scheme and organizational attractiveness. In this case, digital tools and ICTs are exploited to overcome the limitations imposed by Covid-19 (Ashiq et al, 2022), giving a sense of normality to the exchange between users and libraries and adding to the users' experience through positive emotions and sensations (Coker, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…In this case, digital tools and ICTs are exploited to overcome the limitations imposed by Covid-19 (Ashiq et al. , 2022), giving a sense of normality to the exchange between users and libraries and adding to the users' experience through positive emotions and sensations (Coker, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…A literature review found that negative perceptions prevail and their work is misunderstood (Vassilakaki;Moniarou-Papaconstantinou, 2014). Particularly, the emotional factor attached to the personal relationship with (potential) users is of relevance (Consonni, 2010;Coker, 1993;). Overall, the use of the library is directly related with the images and perceptions that individuals and library funders hold of libraries, library services and the librarian profession (Green, 1994;Coker, 1993).…”
Section: Contextmentioning
confidence: 99%
“…Particularly, the emotional factor attached to the personal relationship with (potential) users is of relevance (Consonni, 2010;Coker, 1993;). Overall, the use of the library is directly related with the images and perceptions that individuals and library funders hold of libraries, library services and the librarian profession (Green, 1994;Coker, 1993). Coker states that it is not only negative images and perceptions that need to be overcome but also barriers caused by lack of awareness of the "library world" and unrealistic expectations.…”
Section: Contextmentioning
confidence: 99%
See 1 more Smart Citation